2011
DOI: 10.1259/dmfr/83507370
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of computational measurement of the condyles on digital panoramic radiographs

Abstract: This study has demonstrated that (1) the height of the condyle can be rapidly and reliably assessed using a specific computer system directly on digital panoramic radiographs; (2) although less reliable, area and perimeter can also be acceptably evaluated; and (3) this method has the potential for being routinely used to monitor changes in clinical follow-up as well as for research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 22 publications
(31 reference statements)
1
23
0
2
Order By: Relevance
“…36 The thresholds were a decrease of 0.16 mm 2 for area, 0.34 mm for perimeter, and 0.04 mm for height.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…36 The thresholds were a decrease of 0.16 mm 2 for area, 0.34 mm for perimeter, and 0.04 mm for height.…”
Section: Discussionmentioning
confidence: 93%
“…In the majority of cases, this association was found by using CT and by assessing qualitative changes, such as bone flattening, bone erosion, and osteophyte formation, rather than by quantifying dimensional changes. [31][32][33][34][35][36][37][38][39] Some investigators have suggested that untreated TMJ internal derangement, such as DD, as well as osteoarthritis could act as negative factors in postoperative outcomes for the TMJ. 5,6 Link and Nickerson found signs of arthrosisdbased on conventional radiographydin 50% of patients with a follow-up greater than 12 months after orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the technique used for the condylar head height, perimeter and area calculation in the present series have been extensively described previously by Momjian et al 14 The measurements were made by the same investigator (AM) before surgery (m 1 ), 1 day after surgery (m 2 ) and 1 year after surgery (m 3 ).…”
Section: Computer Image Analysismentioning
confidence: 99%